2018
DOI: 10.1038/s41598-018-28296-y
|View full text |Cite
|
Sign up to set email alerts
|

Spermine increases acetylation of tubulins and facilitates autophagic degradation of prion aggregates

Abstract: Autolysosomal dysfunction and unstable microtubules are hallmarks of chronic neurodegenerative diseases associated with misfolded proteins. Investigation of impaired protein quality control and clearance systems could therefore provide an important avenue for intervention. To investigate this we have used a highly controlled model for protein aggregation, an in vitro prion system. Here we report that prion aggregates traffic via autolysosomes in the cytoplasm. Treatment with the natural polyamine spermine clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 78 publications
1
22
1
Order By: Relevance
“…However, as discussed above, protein-only recPrP Sc would be expected to be structurally similar to cofactor recPrP Sc , and both of these recombinant conformers lack PTMs such as sialylation, which can influence protein clearance [67, 68]. Therefore, it difficult to envision how cellular prion clearance mechanisms, such as autophagy [6972] or uptake by resident innate immune cells [7375], could specifically distinguish between these two conformers. A more likely explanation is that PMCA experimental conditions allow BV PrP C to be more structurally accommodating in vitro than in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…However, as discussed above, protein-only recPrP Sc would be expected to be structurally similar to cofactor recPrP Sc , and both of these recombinant conformers lack PTMs such as sialylation, which can influence protein clearance [67, 68]. Therefore, it difficult to envision how cellular prion clearance mechanisms, such as autophagy [6972] or uptake by resident innate immune cells [7375], could specifically distinguish between these two conformers. A more likely explanation is that PMCA experimental conditions allow BV PrP C to be more structurally accommodating in vitro than in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation and aggregation of misfolded proteins are hallmarks of neurodegenerative diseases, such as AD, FTD, and prion diseases. Interestingly, spermine increases the acetylation of microtubules (enhancing microtubule stability) and facilitates autophagic degradation of prion aggregates (Phadwal et al 2018) . Our preliminary work has demonstrated that polyamines (spermine in particular) decrease tau aggregation and promote microtubule assembly (Hunt et al 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…Using rTg4510 mice bearing the human tau P301L mutation, Hunt et al (2015a) demonstrated that sustained arginase I overexpres-sion over a 4-month period from the beginning of brain tau deposition markedly reduced tau pathology and several kinases capable of phosphorylating tau and mitigated hippocampal atrophy in this mouse model of forebrain tauopathy. It has been shown that polyamines are critically involved in microtubule assembly and stabilization (Savarin et al 2010 ; Hamon et al 2011; Song et al 2013), and the high-order polyamine spermine increases the acetylation of microtubules and facilitates autophagic degradation of prion aggregates (Phadwal et al 2018). Moreover, our recent preliminary work demonstrated that polyamines (spermine in particular) decreased tau aggregation and promoted micro-tubule assembly (Hunt et al 2015b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have also con rmed the declined levels of Sirt3 in the brain tissues of several scrapie infected mice and in SMB-S15 cells, leading to increases of acetylating forms of SOD2 and ATP5β that subsequently induce increase of intracellular ROS and reduction of ATP [20]. Aberrant alterations of acetylation modi cations for other proteins have been also found in the brain tissues or the models in vitro of several neurodegenerative diseases, e.g., tau, microtubules, SOD1 [21][22][23]. However, the global change of protein acetylation in the brain tissues of prion diseases remains unsettled.…”
Section: Introductionmentioning
confidence: 59%